2018
DOI: 10.1681/asn.2017111213
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antibiotic Exposure and Kidney Stone Disease

Abstract: Although intestinal and urinary microbiome perturbations are associated with nephrolithiasis, whether antibiotics are a risk factor for this condition remains unknown. We determined the association between 12 classes of oral antibiotics and nephrolithiasis in a population-based, case-control study nested within 641 general practices providing electronic health record data for >13 million children and adults from 1994 to 2015 in the United Kingdom. We used incidence density sampling to match 25,981 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 40 publications
4
72
0
1
Order By: Relevance
“…The results of this study are consistent with 2 recent case-control studies from Tasian et al 14 and Zampini et al, 15 which found that oral antibiotic use was associated with increased odds of kidney stones among children and adults. Zampini et al 15 found that adults with an active episode of nephrolithiasis were significantly more likely to have taken oral antibiotics in the last year, but not the last 30 days, compared with individuals with no history of the disease.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are consistent with 2 recent case-control studies from Tasian et al 14 and Zampini et al, 15 which found that oral antibiotic use was associated with increased odds of kidney stones among children and adults. Zampini et al 15 found that adults with an active episode of nephrolithiasis were significantly more likely to have taken oral antibiotics in the last year, but not the last 30 days, compared with individuals with no history of the disease.…”
supporting
confidence: 92%
“…In the Zampini study, both oral antibiotic use and incidence of nephrolithiasis were more associated with the urinary tract microbiome than the gut microbiome. Using incidence density sampling, Tasian et al 14 examined 25,981 patients with nephrolithiasis that were matched to 259,797 controls on age, sex, and practice at the date of diagnosis. The adjusted odds ratios for nephrolithiasis were 2.33 for sulfas, 1.88 for cephalosporins, 1.67 for fluoroquinolones, 1.70 for nitrofurantoin, and 1.27 for broad-spectrum penicillins.…”
mentioning
confidence: 99%
“…Similar increases in prevalence exist in a variety of systemic diseases, such as diabetes, cardiovascular disease and metabolic syndrome [4][5][6]. Moreover, a recent population-based study demonstrated that multiple classes of oral antibiotics exposure is associated with increased odds of nephrolithiasis [7]. Interestingly, human microbiome could be affected by all these factors, indicating its potential role in the pathophysiology of nephrolithiasis.…”
Section: Introductionmentioning
confidence: 83%
“…The mammalian intestinal microbiota can partially protect against oxalate toxicity by oxalate degradation [15][16][17][18]. Two recent large-scale epidemiological studies associated antibiotic use with increased nephrolithiasis risk [19,20], presumably via a perturbed microbiota [21]. Multiple gut microbes can degrade oxalate [22], including Oxalobacter formigenes, an oxalate autotroph [23][24][25][26][27].…”
Section: Mainmentioning
confidence: 99%